Konstrukční návrh jednoúčelového stroje na krácení rostlinných stébel - Žižka, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Tato bakalářská práce se zabývá konstrukčním návrhem jednoúčelového stroje na krácení rostlinných stébel. Úkolem stroje je nastříhat již částečně zkrácená a listů zbavená pšeničná stébla na požadovanou délku. Provoz stroje je plně automatizován, obsluha pouze zajišťuje zásobování stroje polotovary, odebírá hotová stébla a kontroluje chod stroje. V práci je vypracována rešerše popisující existující technologie používané pro krácení rostlinných stébel, možnosti pohonu jednoúčelového stroje a možná řešení dopravy stébel. Součástí rešerše je také rozbor potřebných mechanických a fyzikálních vlastností pšeničných stébel. Následně je provedena analýza informací z rešeršní části práce a definování důležitých parametrů pro konstrukční rozvahu. V praktické části práce jsou vypracovány koncepty možných řešení jednotlivých konstrukčních uzlů a zdůvodnění volby jednotlivých řešení. Druhá část praktické části se zabývá konstrukčním řešením vybraného koncepčního návrhu včetně výpočtů. Práce ukazuje možné řešení konstrukce stroje pro zpracování polotovarů s velkou tvarovou rozmanitostí.

This bachelor thesis deals with the design of a single-purpose machine for cutting plant stems. The task of the machine is to cut already partially shortened and stripped wheat straw stalks to the required length. The operation of the machine is fully automated, the operator only ensures the supply of semi-finished products to the machine, removes the finished stalks and controls the operation of the machine. In the thesis is a search describing the existing technologies used for cutting plant stalks, the possibility of driving a single-purpose machine and possible solutions for transporting stalks. The research also includes an analysis of the necessary mechanical and physical properties of wheat stalks. Subsequently, the analysis of information from the research part of the thesis and the definition of important parameters for the design construction balance sheet is performed. In the practical part of the work are developed concepts of possible solutions of individual structural nodes and justification of the choice of individual solutions. The second part of the practical part deals with the construction design of a selected conceptual design, including calculations. The work shows a possible solution for the construction of a machine for processing semi-finished products with a large variety of shapes.
Design of single-purpose cutting machine for shortening of plant stems
Keywords: krácení; stébla; jednoúčelový stroj; sláma; shortening; stalks; single-purpose machine; straw